The pros and cons of the QuantiFERON test for the diagnosis of tuberculosis, prediction of disease progression, and treatment monitoring. Issue 2 (June 2016) - Ndzi, Elvis Ndukong; Nkenfou, Celine Nguefeu; Gwom, Luc Christian; Fainguem, Nadine; Fokam, Joseph; Pefura, Yone
Abstract: Objective/Background: Tuberculosis (TB) is a re-emerging disease with the advent of human immunodeficiency virus/AIDS infections. Discovered in 1959, diagnosed by various approaches and treated with antibiotics, the treatment of TB infection still poses public health concerns. Many cases of resistance and cross-resistance are observed. Diagnosis by culture, which is considered as the standard method, takes too long (20–30 days) and is not suitable for extrapulmonary TB. QuantiFERON test, which is an indirect immunoassay based on blood, was developed. Much hope was placed in this new approach because it is based on blood, and many research teams have used it. We discuss the results of these different research groups who have used QuantiFERON for diagnosis, prediction of disease progression, or monitoring patients during the treatment of TB. Methods: Articles published in PubMed and documents published on Google were searched with the keywords: diagnosis and TB and QuantiFERON; TB and QuantiFERON and therapeutic monitoring; interferon-γ release assay; disease progression. These articles were read and analyzed. Results: The results were controversial with regards to using the QuantiFERON test for the diagnosis of TB according to the study population (ethnic group, bacillus Calmette–Guérin vaccine use) and according to the state of the immune system of the people studied (human immunodeficiency virus immunosuppression in cancer medication, hypertension). Also, research findings were controversial with regards to using QuantiFERON for monitoring TB patients on anti-TB medications. Also, the predictive positive value for the progression to TB among immigrant close contacts of both interferon-γ release assays was not better than that of the tuberculin skin test. Conclusion: The QuantiFERON has advantages and limitations depending on the type of population studied. Recommendations are made to improve the sensitivity and specificity and to differentiate between latent and active TB by adding other specific proteins in the Mycobacterium tuberculosis antigen cocktail.